PENGARUH PEMBERIAN AIR CUCIAN BERAS DAN SERBUK CANGKANG KEONG MAS TERHADAP PERTUMBUHAN VEGETATIF TANAMAN SELADA ( LACTUCA SATIVA L) PADA HIDROPONIK SISTEM WICK - Reny Afriera; Kartika Manalu; Rahmadina (LPPM Universitas Cipta Mandiri, 2024)
This study aims to know the effect of liquid organic nutrients on lettuce plant growth using axis hydroponics. The method used in this study was a factorial Completely Randomized Design (CRD). The treatments consisted of 4 types of treatment, namely P0 (control) with ABmix nutrition (15ml A + 15 ml B/liter), P1 with rice washing waste water (3,000 mL), P2 with POC administration of snail shells (30ml/liter). L), P3 by giving rice washing water + Conch Shell POC with each treatment repeated 6 times. Parameters observed were plant height, number of leaves, leaf width, leaf length, and plant wet weight. The data obtained will be analyzed using the One Way ANOVA (Analysis of Variance) statistical test and then continued with further tests. The data were analyzed using SPSS. The results showed that P0 (ABmix) and P3 (ACB+POC snail powder) had better results because they showed higher results for all observation parameters compared to other treatments. the treatment that has been carried out has a significant effect on the observation parameters, starting from the treatment that gives the best results to the treatment that gives the lowest results, namely P0 (ABmix), P3 (Waste Rice Washing Water + Conch Shell POC), P1 (Waste Washing Water) Rice), and P2 (Snail Shell POC).